Students` Perception toward Mobile-Assisted Language Learning (MALL) in English Speaking Class - Rakhmanina, Lisa; Melati, Melati; Masitah , Siti (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objectives of the study emphasize on finding out the students` perception on the use of several tools in English Speaking class to support the English speaking learning activities, the positive and negative values that could engage students in English speaking learning during the pandemic. The study was a descriptive study that involved 30 students in Faculty of Law in University of Prof. Hazairin, SH. The data was collected through a questionnaire, online observation and interview.  The findings of the study stated that students showed positive perception toward the use of several tools in English speaking class. They believed that offline dictionaries, Video blogging, Instagram, YouTube could support and motivate them more in their English speaking classes. The findings also discovered some values related to the study. They showed positive values in accepting the modernization, practicality, and portability of using Offline dictionary, Video blogging, Instagram, YouTube and Zoom. The unsocialized trait and unbalanced emphasis are several of the disadvantages. Keywords: Mobile-Assisted Language Learning MALL, Speaking, Pandemic